Ionization and double-excitations within the framework of the G-particle-hole hypervirial equation method - Valdemoro, Carmela (2012)
Recently, through the use of one-electron excitation operators, the set of low-lying excited states of several electronic systems was obtained within the framework of the Hermitian Operator method combined with the G-particle-hole Hypervirial equation method [Valdemoro et al., J. Math. Chem. 2012, 50, 492]. The main aim of this article is to extend our study by including higher-order excitations as well as extended ionization and electron affinity operators. Several examples show the convenience of this extension to improve the accuracy of the results in some relevant cases. Through the use of geminal excitations, the algebra of the formal derivations is considerably simplified. © 2012 Wiley Periodicals, Inc. Given a well-known initial electronic state of an atom or molecule, one may obtain the spectrum of energies corresponding to its single and double excited states. This may be achieved by applying the close-form analytical expressions reported here, which constitute an extension of the well-known Hermitian Operator method. Extended relations for the ionization energies are also reported here. In all these derivations a geminal-second- quantization algebra has been used. Copyright © 2012 Wiley Periodicals, Inc.